The Effect of Contact Time and Adsorbent Dosage and Contact Time of Activated Carbon of Eucalyptus Oil Refining on Ammonia Levels (NH3) Leather Industry Liquid Waste - Dardiri, Fadiya Ananda; Hidayati, Nasrul; Wahyuningsih, Sri (International Journal of Health Literacy and Science, 2024)
Indonesia's industry expands to suit domestic demand as the populationincreases. One of these is the leather processing business, which heavilyrelies on both chemicals and water in its operations. Adsorption was theapproach employed in this investigation. The purpose of this study is toestablish the ideal contact dosage and contact time for ammonia wasteadsorption. The Adsorbent characterisation test results have beendiscovered. The findings of the ammonia adsorption test with dosevariation showed that, at a dosage of 2.5 grams and a removal rate of 92%,HCl 0.36 M activated carbon was more efficient than other activatedcarbon. The HCl 0.036 M activated carbon was shown to be more efficientthan activated carbon in the time variation ammonia level adsorption test,with an elimination rate of 82.48% after 25 minutes. Activated carbonsand HCl 0.36 M activated carbons follow the pattern of the Langmuirisotherm equation and are reversible, according to the results of isothermtests of dosage and time variations (reversible).